Atypical extra nasopharyngeal angiofibroma in an unusual location: tonsil posterior pillar (oropharynx) - Mittal, Shweta; Priya, Madhu; Varshney, Saurabh; Angral, Sumeet; Xavier, Joyson; Malhotra, Manu; Bhardwaj, Abhishek; Kumar, Amit; Tyagi, Amit Kumar (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Angiofibroma is a benign, locally aggressive highly vascular tumor that typically affects young adolescent males and has a pathognomonic epicenter of origin in the nasopharynx. The atypical angiofibromas share the same histological features as that of Juvenile nasopharyngeal angiofibroma, however they differ significantly in their clinical features. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Here we are reporting a very rare case of atypical angiofibroma in an adult male presenting as a non-vascular mass in the oropharynx with posterior pillar as the subsite. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 26-years old male patient presented with chief complaints of foreign body sensation and mass in throat for one and a half months which was gradually progressive in size. Histopathological examination revealed a lesion with an intricate mixture of blood vessels, irregular fibrous stroma with loose edematous and fibrous area along with multinucleated stromal cells which was suggestive of angiofibroma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Oropharyngeal angiofibroma, being an atypical angiofibroma in terms of site and presenting complaints, presents a diagnostic challenge. Though rare, it should always be kept as a differential diagnosis in any oropharyngeal mass irrespective of its vascularity, typical age or sex of the patient.